A short-term increase in cancer risk associated with daytime napping is likely to reflect pre-clinical disease: Prospective cohort study - Cairns, B; Travis, R; Wang, X; Reeves, G; Green, J; Beral, V (2012)
Background: Sleep disturbance, a correlate of which is daytime napping, has been hypothesised to be associated with risk of breast and other cancers.Methods:We estimated relative risks (RR) of breast and other invasive cancers by the reported frequency of daytime napping in a large prospective cohort of middle-aged women in the UK.Results:During an average of 7.4 years of follow-up, 20 058 breast cancers and 31 856 other cancers were diagnosed. Over the first 4 years of follow-up, daytime napping (sometimes/usually vs rarely/never) was associated with slightly increased risks of breast cancer (RR1.10, 95% CI 1.06-1.15) and of other cancers (RR1.12, 1.08-1.15), but the RRs decreased significantly with increasing follow-up time (P<0.001 and P<0.01, respectively, for trend). Four or more years after baseline, there was no elevated risk of breast cancer (RR1.00, 0.96-1.05), and only marginally greater risk of other cancers (RR1.04, 1.01-1.07).Conclusion:The effect of pre-clinical disease is a likely explanation for the short-term increased risk of breast and other cancers associated with daytime napping. © 2012 Cancer Research UK All rights reserved.